Does hospital medical staff maintain hospital disaster resilience? - Georgieva Georgieva, Mariya; Stefanov Kostadinov, Rostislav; Anastasova Semerdjieva Filipova, Mariya (Vojnosanitetski pregled, 2024)
Background/Aim. In the event of a disaster, it is necessary for medical personnel to demonstrate the operational component of disaster resilience, which requires certain knowledge and skills regarding disaster medical response algorithms. The aim of this study was to analyze the preparedness of hospital’s healthcare staff for maintaining hospital disaster resilience. Methods. An anonymous survey was conducted from July to September 2019 among 295 medical staff employed in hospitals in the territory of the city of Plovdiv, Bulgaria. Pearson’s Chi-square test, Student’s t-test, and graphical analysis were used in the statistical analysis. Results. Most of the medical staff, i.e., 85.8%, believed that disaster drills are not held regularly in hospitals, 30.8% thought that the training period was shorter than two years, and the majority, i.e., 86.1%, did not participate in exercises. Conclusion. Due to the irregular implementation of exercises and the small number of participants in them, the level of preparedness for responding to disasters is not maintained at a high level in hospitals in the Plovdiv region. Therefore, it is necessary to introduce a specific training program and exercise once a year, which should have a beneficial effect on increasing the preparedness of the medical staff for disasters and improving the operational resilience of the hospital.
Keywords: bulgaria; disaster planning; hospitals; personnel, hospital; surveys and questionnaires.